Prevalence and genetic diversity of potato virus Y strains in Pakistani potato fields: insights from partial sequence analysis - Shahid, Muhammad Hamza; Sahi, Ghulam Mustafa; Naveed, Zunaira Afzal; Ali, Safdar; Wahab, Muhammad; Sagheer, Muhammad; Mustafa, Azher (Journal of plant diseases and protection (2006), 2025)
Potato virus Y (PVY) is the fifth most economically important plant virus and continues to remain an existential threat to the potato crop around the world. Its inherent ability to rapidly develop new strains is the major cause of concern. Therefore, PVY-infected samples were collected by surveying the core potato-growing areas and subject to molecular characterization to determine the status of PVY strains. Blast analysis of partial sequences of PVY isolates identified them with three strains, i.e., PVY NTN , PVY N−Wi and PVY-SYR-II which have been found to be prevalent in potato-growing districts which are largely exotic in nature. The study resulted in detection and discovery of PVY N−Wi and PVY-SYR-II strains for the first time in major potato-growing regions of Pakistan. Their phylogeny identifies them with exotic PVY strains. The study suggests strong quarantine and screening measures must be in place to prevent potential entrance of exotic strains through imported seed potato. This study will help farmers cope with emerging challenges to the potato crop.